A false tranquility - Yang, Yanmeng (Nanyang Technological University, 2023)
The entire project is inspired by a song called ‘A False Tranquility’ which indicated the tragic life of Li Yu, the last emperor in Southern Tang era - He is a great poet but not a successful king, the Tang empire has fallen after he ascended the throne. His political insensitivity resulted in his negligence of threats and wars. When the danger has come, he is not powerful enough to fight back but to use his calligraphy as his weapon to record the viciousness of the enemy, then he died by poison on orders of Emperor Taizong of Song(Zhao Kuangyin) after 2 years as an exiled prisoner.Obviously, the collapsing regime of Tang era and his limited ability have hastened the demise of the Tang Dynasty. This story is considered as a short narrative with a fantasy content, in this case, the time travelling. It tells a naughty boy accidentally traveled through the dimension and witnessed the life that a historical figure, Li Yu, the last emperor of Tang era, had encountered.The naughty boy's rebellious adolescence, dislike of learning and strong curiosity for everything contributed to his time travel through the time dimension, which may have changed his attitude towards learning.